2018
DOI: 10.31538/nzh.v1i1.41
|View full text |Cite
|
Sign up to set email alerts
|

Konsep Tarbiyah, Ta’lim Dan Ta’dib Dalam Al-Qur’an

Abstract: This research is motivated by various conceptions about education in Islam isapparently has the uniqueness of the meaning contained in Al-Qur'an and Al-Hadith, because it shows the richness of the meaning of the words in the verses and every sentence. Educational concepts or theories experience a heated debate for 'lim and Ta'dib. The research method used is literature research and qualitative descriptive analysis with philosophical approach. The result of the research is that the language is from the same roo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
8

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 0 publications
0
10
0
8
Order By: Relevance
“…Education and teaching in Arabic is "tarbiyah wa ta'lim", while Islamic education in Arabic is "tarbiyatul islamiyah". From this etymological meaning, it can be concluded that Tarbiyah means an effort made to maintain and develop children's potential based on their talents, and exert all efforts in developing these potential gradually to achieve perfection (Ridwan, 2018). (Syalabi, 1997).…”
Section: Homeschooling In Islamic Education Perspectivementioning
confidence: 99%
“…Education and teaching in Arabic is "tarbiyah wa ta'lim", while Islamic education in Arabic is "tarbiyatul islamiyah". From this etymological meaning, it can be concluded that Tarbiyah means an effort made to maintain and develop children's potential based on their talents, and exert all efforts in developing these potential gradually to achieve perfection (Ridwan, 2018). (Syalabi, 1997).…”
Section: Homeschooling In Islamic Education Perspectivementioning
confidence: 99%
“…Subjek penelitian dalam penelitian ini menggunakan tekhnik purposive dimana pengambilan subjek penelitian didasarkan atas makna dan tujuan penelitian (Creswell, 2012;Lexy J, 2011;Suharsimi, 2016). Adapun subjek penelitiannya adalah kepala madrasah, guru, dan peserta didik Madrasah Tsanawiayah Unggulan Hikmatul Amanah BendunganJati, Pacet-Mojokerto.…”
Section: Metode Penelitianunclassified
“…Kepedulian masyarakat sangat dibutuhkan dalam hal pengembangan pendidikan, bukan hanya seperti sekarang yang sebagian besar memberi bantuan material saja, namun seharusnya perlu menyisihkan waktunya juga agar dapat membantu lembaga pendidikan minimal berupa ideide kreatif, gagasan yang inovatif demi kemajuan kualitas suatu sekolah. Oleh karena itu, masyarakat merupakan salah satu bagian penting dari lembaga pendidikan yang akan ikut andil sebagai stakeholder pendidikan (Ridwan, 2018).…”
Section: Pendahuluanunclassified